2020
DOI: 10.1080/21505594.2020.1772653
|View full text |Cite
|
Sign up to set email alerts
|

Arachidonic acid metabolism is elevated inMycoplasma gallisepticumandEscherichia colico-infection and induces LTC4 in serum as the biomarker for detecting poultry respiratory disease

Abstract: Outbreaks of multiple respiratory diseases with high morbidity and mortality have been frequently reported in poultry industry. Metabolic profiling has showed widespread usage in metabolic and infectious disease for identifying biomarkers and understanding of complex mechanisms. In this study, the non-targeted metabolomics were used on Mycoplasma gallisepticum ( MG ) and Escherichia coli ( E.coli ) co-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 46 publications
(46 reference statements)
1
19
0
Order By: Relevance
“…The concentration of E. coli was adjusted to 10 9 CFU/mL before infection. The detection of the density for MG and E. coli were consistent as explained in our previous study ( Wu et al., 2020 ; Wu et al., 2019b ). Baicalin (purity ≥ 98.0%) was bought from Huifeng Animal Health Co., Ltd. (Heilongjiang, China).…”
Section: Methodssupporting
confidence: 91%
See 2 more Smart Citations
“…The concentration of E. coli was adjusted to 10 9 CFU/mL before infection. The detection of the density for MG and E. coli were consistent as explained in our previous study ( Wu et al., 2020 ; Wu et al., 2019b ). Baicalin (purity ≥ 98.0%) was bought from Huifeng Animal Health Co., Ltd. (Heilongjiang, China).…”
Section: Methodssupporting
confidence: 91%
“…Similarly, avian pathogenic E. coli also induced pathological changes and caused severe lung damage ( Peng et al., 2019 ). Several studies examined histopathological changes in lungs and mucosal respiratory epithelium with increased inflammation in coinfection of MG with other respiratory pathogens including E. coli ( Stipkovits et al., 2012 ; Xiao et al., 2014 ; Sid et al., 2015 ; Wu et al., 2020 ). In the present study, increased expressions of inflammatory cytokines were observed in chicken lung in MG or E. coli single or mixed infection group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both strains of APEC activated inflammatory and immune signalling pathways in these immune cells, yet genes from the aryl hydrocarbon receptor pathway, IL-17 and STAT3 signalling, and heterophil recruitment pathways responded differently to APEC O2 than APEC O1, illustrating that different APEC serotypes do not necessarily induce the same host immune responses. Serum metabolomics from White Leghorn chickens co-infected with APEC and Mycoplasma gallisepticum observed changes in arachidonic acid metabolism and increased levels of leukotriene C4 (Wu et al, 2020), while the lung transcriptome from the same experiment identified a role for IL-17 signalling during co-infection (Wu et al, 2019). Other experiments used transcriptomics to measure responses to in vitro APEC infection; an immune-focused microarray was used on chicken monocyte-derived macrophages to detect large changes in antimicrobial genes, cytokines, and cytokine receptors (Lavrič et al, 2008), while RNA-seq on chicken type II pneumocytes, epithelial cells that regulate lung immunity, identified differential expression in apoptosis, NF-κB, and cytokine signalling pathways (L.Y.…”
Section: Functional Genomicsmentioning
confidence: 99%
“…Due to the intensi cation of commercial poultry production, explosive multiple respiratory infections have become an urgent problem [16]. This co-pathogenesis is characterized by complex interactions between co-infection pathogens and the host [17,18].…”
Section: Introductionmentioning
confidence: 99%